Design and Analysis of a 10 MW On-Grid Solar Power Generation System in Lhokseumawe with Variation of Tilt Angle and Interrow Spacing - Nazmi Roan Pratama; Muchlis Abdul Muthalib (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
The primary focus of this study is to develop a ground-mounted solar power generation system with the optimal tilt angle and inter-row spacing to generate electricity in Indonesia, specifically in Lhokseumawe City. The research involves conducting simulation tests using Meteonorm software for solar resource assessment. Additionally, the HelioScope software is employed for modeling the ground-mounted solar power generation system, analyzing the PV system's performance in terms of annual generation, system losses, and performance ratio, as well as studying the solar panel's performance, current-voltage, and power-voltage curves for varying irradiance levels. The Single Line Diagram (SLD) reveals that 12 strings are connected to each inverter, and the output power of inverters is combined using 20.0 A circuit interconnects. The efficiency of solar power generation systems is influenced by the tilt angle and interrow spacing. Based on the simulation results for all scenarios, it is concluded that the solar power generation system installed at 0° tilt angle with a 0.9-meter interrow spacing outperforms other solar power generation systems. This is attributed to the maximum total collector irradiance of 1731.6 kWh/m2 compared to other tilt angles. At 0° tilt angle, the annual production of the solar power generation system is 14.77 GWh, with a performance ratio of 80.6%. This research aims to provide valuable insights for energy system designers, planners, and investors, guiding the development of strategies for the implementation of solar power generation energy systems not only in Indonesia but also globally.